Utilization of Canva Application as an Innovative Learning Media at Al-Wahdah Kindergarten, Bandung City: Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Inovatif di TKAl-Wahdah Kota Bandung - Endang Komara; Maulana, Yana; Lina Dalina; Abdul Rahman (Universitas Lancang Kuning, 2024)
Early Childhood Education (ECE) teachers must master the Canva for Education platform, as this tool offers significant benefits in executing teaching tasks and guiding the development of young children. Proficiency in Canva for Education equips ECE teachers with an effective tool to create innovative and engaging learning experiences that cater to the needs of young children. Additionally, it aids in enhancing the competitiveness and relevance of ECE institutions in the current digital era. Furthermore, with Canva, teachers can easily tailor learning materials to suit the needs and comprehension levels of each child. This allows for the personalization of teaching approaches, addressing individual differences and facilitating optimal growth and development. The objective of this service is to provide training and guidance to the School Principals, Teachers, and Education Staff of TK AL-Wahdah in utilizing the Canva facilities available within the belajar.id account. The training, attended by 12 individuals, resulted in an improvement in knowledge and skills regarding the utilization of the Canva application for instructional material creation. The participants' responses were highly positive as they directly experienced the benefits of using the Canva application to support the learning process in the school.